What should be the strategy of Wipro to position itself as one of the Top 5 IT consulting partners in the Banking sector of European region ? - CHAKRABORTY, RAHUL (2014)
“Everything is amazing right now and nobody’s happy or satisfied (LOUIS, 2014)”. If this can be asked to any of the BFSI (Banking and Financial institution) firms across Europe - “what is that one thing they are worried about at this very moment?” –they will say profitability. Average return on Equity of the BFSI firms in Europe is trading in single digit (KPMG , 2014). Economic conditions across Europe has been improving since 2011 and with a changing demand of technology focused customers, the medium and small sized BFSI firms are replacing their legacy IT systems with advanced IT systems but struggling to get the best value for investment. They are now being dependent on the IT consulting practices of different management consulting firms since selecting the best IT system is not a core competency of these banks, however to sustain in this competitive market they need best systems or systems which can produce necessary business solutions which should be quicker and reliable as well. These consultancy firms do charge higher premiums.